2021
DOI: 10.22331/q-2021-05-27-461
|View full text |Cite
|
Sign up to set email alerts
|

Spectrally multimode integrated SU(1,1) interferometer

Abstract: Nonlinear SU(1,1) interferometers are fruitful and promising tools for spectral engineering and precise measurements with phase sensitivity below the classical bound. Such interferometers have been successfully realized in bulk and fiber-based configurations. However, rapidly developing integrated technologies provide higher efficiencies, smaller footprints, and pave the way to quantum-enhanced on-chip interferometry. In this work, we theoretically realised an integrated architecture of the multimode SU(1,1) i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 48 publications
0
26
0
Order By: Relevance
“…The presence of this noise is caused by the fact that our technique for compensating the group velocities of signal and idler photons succeeds in the proximity of the central frequencies (namely, where the main peaks of the intensity spectra are expected), whereas it fails for frequencies far from ω s0 and ω i0 , resulting in the emergence of residual photons. The same issue was already observed in the degenerate SU(1,1) interferometer [28]. In both degenerate and two-colour frameworks, the presence of this residual radiation hinders the perfect interference and, therefore, affects the precision of the interferometer, which can be estimated by means of the phase sensitivity [14]:…”
Section: Dispersion Suppression and Phase Sensitivitymentioning
confidence: 56%
See 4 more Smart Citations
“…The presence of this noise is caused by the fact that our technique for compensating the group velocities of signal and idler photons succeeds in the proximity of the central frequencies (namely, where the main peaks of the intensity spectra are expected), whereas it fails for frequencies far from ω s0 and ω i0 , resulting in the emergence of residual photons. The same issue was already observed in the degenerate SU(1,1) interferometer [28]. In both degenerate and two-colour frameworks, the presence of this residual radiation hinders the perfect interference and, therefore, affects the precision of the interferometer, which can be estimated by means of the phase sensitivity [14]:…”
Section: Dispersion Suppression and Phase Sensitivitymentioning
confidence: 56%
“…The regime of destructive interference is very important for reducing noise and improving phase sensitivity in SU(1,1) interferometers [8]. Analysing a degenerate multimode SU(1,1) interferometer, we already found that the shape of the JSI and the number of generated photons at different imparted phase ϕ are strongly conditioned by the arrangement of various components within the integrated device [28]. In this section, in order to improve the phase sensitivity of the non-degenerate two-colour SU(1,1) interferometer, we elaborate a strategy for reducing the number of generated photons in the destructive interference regime by properly placing polarisation converters.…”
Section: Dispersion Suppression and Phase Sensitivitymentioning
confidence: 98%
See 3 more Smart Citations